1991
DOI: 10.1093/carcin/12.9.1551
|View full text |Cite
|
Sign up to set email alerts
|

A poroposed role for silicates and protein in the proliferative effects of saccharin on the male rat urothelium

Abstract: High doses of sodium saccharin, a non-genotoxic chemical, lead to the formation of silicate-containing precipitate and microcrystals in urine of male rats. Differences in urinary protein, pH, sodium and other factors affect silicate-containing precipitate and microcrystal formation as well as the bladder effects of sodium saccharin. Total urinary silicon concentration (mostly soluble) in sodium saccharin-fed rats is similar to or lower than the concentration in control rats. Binding of saccharin to male rat ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Recently Cohen et al (7) hypothesized that a2u-globulin, which is synthesized in the male rat liver and excreted into the urine in large quantities, may be a necessary component for promotion of rat urinary bladder carcinogenesis. Indeed, it has been shown that NBR male rats that lack a2u-globulin-synthesizing ability do not demonstrate the expected increases in epithelial cell proliferation after sodium saccharin and Na-AsA treatment (26,49).…”
Section: Methodsmentioning
confidence: 99%
“…Recently Cohen et al (7) hypothesized that a2u-globulin, which is synthesized in the male rat liver and excreted into the urine in large quantities, may be a necessary component for promotion of rat urinary bladder carcinogenesis. Indeed, it has been shown that NBR male rats that lack a2u-globulin-synthesizing ability do not demonstrate the expected increases in epithelial cell proliferation after sodium saccharin and Na-AsA treatment (26,49).…”
Section: Methodsmentioning
confidence: 99%
“…As early as 8 days after the chemical was removed, light microscopic examination of urine collected on study day 79 from animals in the recovery group showed no evidence of the small round crystals found in the urine of the animals during treatment with 5,000 or 20,000 ppm sulfosulfuron. The only crystals present on urinary lters prepared from the same urine and examined by SEM and X-ray energy dispersive spectroscopy had the characteristic cof n-shaped morphology, and X-ray spectrum of ammonium magnesium phosphate crystals normally found in rat urine (9).…”
Section: Recovery Periodmentioning
confidence: 96%
“…68,69 Saccharin is not genotoxic; the presumed mechanism of toxicity is the binding of saccharin to urinary proteins (not normally found in humans), creating a nidus for the formation of silicate crystals, which are cytotoxic to bladder epithelium. 70 Saccharin is an o-toluene sulfonamide derivative and causes similar dermatologic reactions. Crosssensitivity with sulfonamides has been demonstrated; therefore, children with "sulfa" allergy should also avoid saccharin.…”
Section: Saccharinmentioning
confidence: 99%